Consumer Products Nerve Injuries Among Patients Products Presenting to United States Emergency Departments Between 2012 and 2021: A Nationwide Cohort - Ganga A; Mukhdomi T; Kim EJ; Ly E; Patel Y; Dankievitch KN; Kendall MC (Open Access Emergency Medicine)
Arjun Ganga,1 Taif Mukhdomi,2 Eric J Kim,1 Eric Ly,3 Yash Patel,3 Korinne N Dankievitch,3 Mark C Kendall3 1Warren Alpert School of Medicine, Brown University, Providence, RI, 02903, USA; 2Department of Pain, Pain Zero, New Albany, OH, 43054, USA; 3Department of Anesthesiology, Warren Alpert School of Medicine, Brown University, Providence, RI, 02903, USACorrespondence: Mark C Kendall, Department of Anesthesiology, Warren Alpert School of Medicine, Brown University, 593 Eddy Street, Davol #129, Providence, Rhode Island, 02903, USA, Tel +414-444-5172, Email mark.kendall@lifespan.orgIntroduction: Nerve injuries and resultant pain are common causes of emergency department (ED) visits in the United States. Injuries often occur either due to activity (ie sports related injury) or due to consumer products such as stairs or bedframes. We investigated the incidence of consumer product-related nerve injuries (CPNIs) in patients who presented to the ED in the United States.Materials and Methods: The National Electronic Injury Surveillance System was queried to identify patients presenting to US EDs between 2012 and 2021 with CPNIs. The cohort was categorized by age: 1) 0– 17-year-olds, 2) 18– 64-year-olds, 3) and 65+ year-olds. The primary outcomes were the type of injury and the location of injury.Results: A total of 14,410 CPNIs were reported. There was an increase in yearly CPNIs (β = 4763, (95% confidence interval 1940– 7586); P = 0.004). The majority (11,547/14,410, 80.1%) of injuries were among adults. Elderly females encountered more CPNIs than males (52.5% vs 47.8%, P = 0.002). Stairs were most involved in nerve injuries among adults (8.21%) and children (3.96%) whereas beds or bedframe injuries were most frequent (12.0%) among the elderly. Sciatica was the most common diagnosis (≥ 60%) followed by radiculopathy (≥ 20%) in adults > 18 years of age. Among adults aged 18 to 29, the upper trunk, lower arm, and wrist was more frequently involved, while these areas were less commonly involved in adults aged 40 to 49. Compared to adults, the pediatric and elderly patients presented with more traumatic spinal cord injuries.Conclusion: Sciatica, radiculopathy, and traumatic spinal cord injury were the most common diagnoses following CPNIs. Children and the elderly tended to present with more severe CPNIs than the general adult population. Further investigations exploring interventions to lower the burden of CPNIs, improve consumer product safety, and reduce potentially chronic and debilitating injuries are necessary.Keywords: consumer product, nerve injury, emergency departments, traumatic injury